2020
DOI: 10.3389/fcell.2020.590576
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Crosstalk Between MYC and HIF in Cancer

Abstract: The transcription factor c-MYC (MYC thereafter) is a global regulator of gene expression. It is overexpressed or deregulated in human cancers of diverse origins and plays a key role in the development of cancers. Hypoxia-inducible factors (HIFs), a central regulator for cells to adapt to low cellular oxygen levels, is also often overexpressed and activated in many human cancers. HIF mediates the primary transcriptional response of a wide range of genes in response to hypoxia. Earlier studies focused on the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 143 publications
1
51
1
Order By: Relevance
“…All of the aforementioned pathways and molecules have crosstalk with the master regulator and oxygen-sensing transcription factor HIF-1 [ 11 ]. Some examples include the activation of regulatory subunit HIF-1α by Akt and mTOR [ 12 ], the inhibition of Myc by HIF under hypoxic conditions and cooperation between the two molecules to promote cancer cell growth [ 13 ], and the inhibition of HIF-1α via high p53 expression [ 14 ]. This molecular crosstalk is especially important because HIF-1 exerts major effects on glucose metabolism when active.…”
Section: Glucose Metabolism and The Warburg Effect: A Century Latermentioning
confidence: 99%
“…All of the aforementioned pathways and molecules have crosstalk with the master regulator and oxygen-sensing transcription factor HIF-1 [ 11 ]. Some examples include the activation of regulatory subunit HIF-1α by Akt and mTOR [ 12 ], the inhibition of Myc by HIF under hypoxic conditions and cooperation between the two molecules to promote cancer cell growth [ 13 ], and the inhibition of HIF-1α via high p53 expression [ 14 ]. This molecular crosstalk is especially important because HIF-1 exerts major effects on glucose metabolism when active.…”
Section: Glucose Metabolism and The Warburg Effect: A Century Latermentioning
confidence: 99%
“…The stress-responsive genetic regulator Sirtuin1, which has been shown to have an influence on the stability of HIF-1α expression has also been associated with the regulation of NMYC expression [ 36 , 37 , 38 , 39 ]. In its role as a stabilizer of HIF-1α and HIF-2α expression, it might be hypothezised to be able to contribute to activation of AQP1 in a hypoxia-dependent manner [ 38 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, glutaminase, a key enzyme converting glutamine to glutamate, was found to be increased in several cell types, including osteoblasts [ 84 ] and, via HIF-1, in colorectal cancer cells, which required glutaminase for hypoxia-induced migration and invasion in vitro, and tumour growth and metastatic colonisation in vivo [ 85 ]. The relationship between Myc and HIF is complex [ 86 ]. It has been shown that HIF-1α and HIF-2α have opposing effects on Myc; HIF-1α decreased Myc expression [ 87 ] while HIF-2α promoted c-Myc activity in various cell types [ 88 ].…”
Section: Glutamine Metabolism and Hypoxiamentioning
confidence: 99%